PENGEMBANGAN KEMAMPUAN PARENTING WALI MURID MIM JATISARI DALAM MENUMBUHKAN KESALEHAN ANAK - Muhammad Isa Anshory; M Mujiburrohman; Andi Setiawan; Muhammad Fatih Rizku Najah (AL HAZIQ: Journal of Community Service, 2025)
This Community Service Activity (PKM) was motivated by the low level of parental involvement in the spiritual and moral development of children at home, particularly in the environment of MI Muhammadiyah Jatisari. The purpose of this program is to enhance the Islamic parenting skills of students’ guardians so that they are able to foster children’s piety through the habituation of worship, character cultivation, and effective family communication. The implementation methods include lectures and question–answer sessions. The activity was held on Thursday, February 13, 2025, from 09.00 to 11.00 WIB, with 30 student guardians participating. The results show a significant increase in parents’ understanding of the importance of the family’s role in educating children, as well as an improvement in their practical knowledge of Islamic parenting. Participants demonstrated high enthusiasm and expressed their hope for regular follow-up programs. This program is concluded to be effective in improving the understanding of Islamic parenting and strengthening the synergy between the madrasah and families.